The PD curator : how to design peer-to-peer professional learning that elevates teachers and teaching - Porosoff, Lauren, 1975- (ASCD, 2021)
"The PD Curator is about how professional learning experiences can become more inclusive, participatory, cohesive, and effective-and about the role teachers and leaders can play in creating those experiences"--